Identification of evergreen species in the community of La Cal, municipality of Jinotega - Salinas-Hernández, Bertha Griselda; Huerta, Kleyla Karina; Martínez-Centeno, Ayda Lina (Rev. iberoam. bioecon. cambio clim., 2019)
The objective of this study was to classify, characterize and make an inventory of native evergreen species in the community of La Cal-Jinotega between the August-November period of 2017. We start by asking him why it is important to classify the species that exist in that community and then conduct a forest inventory. The methods used were descriptive, cross-sectional, using the forest inventory as a collection instrument. As a result, we found 8 species of evergreen native trees, but the most common was Cacahuillo, which had been coming from this community for many generations.